Corporate saving and financing decisions in Latin America - Bebczuk, Ricardo Nestor (2000)
This paper studies private saving decisions in Latin America in the 1990s, with special focus on corporate saving. We investigate the puzzling omission of corporate saving in private saving studies, and afterwards we calculate, in several cases for the first time, gross saving and sources of funds of the corporate sector in seven Latin American countries over the period 1990-1996. Also, we conduct a preliminary econometric exploration on the macroeconomic determinants of private and corporate saving, and private investment. Particularly, the effect of capital-market imperfections and the relationship between corporate and personal savings are analyzed.